Data Resources and Services at CAsDC. Issue Volume 9:Issue S298(2013) (6th January 2014) - Cui, Chenzhou; He, Boliang; Xiao, Jian; Yu, Ce; Li, Jian; Cao, Zihuang; Su, Liying; Fan, Dongwei; Qiao, Cuilan; Li, Changhua; Chen, Yue; Wang, Runtao; et al.
Abstract: The Chinese Astronomical Data Center (CAsDC) is a member of World Data System, hosted at National Astronomical Observatories, Chinese Academy of Sciences(NAOC). The CAsDC keeps close collaboration with IVOA, WDS and CODATA. The whole set of LAMOST data, including raw data and data products, are hosted at the CAsDC. Data resources and services of the CAsDC are introduced.